EVALUASI KONDISI LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PABRIK PENGOLAHAN KELAPA SAWIT PT. SENTOSA KALIMANTAN JAYA - Nina Wulandari; Rusli Anwar; Rusmini (JURNAL AGRIMENT, 2020)
The purpose of this study was to determine the working environment conditions for employees and to identify employees in oil palm processing factories. This research uses data analysis techniques by measuring directly in the field, observation and questionnaires and literature studies. Then the analysis used descriptive statistical methods using the data and information obtained. The results showed that of the 7 parameters of the work environment that were measured, there were 4 parameters, namely: ceiling height, ventilation holes and light intensity that met environmental quality standards and there were 3 environmental parameters, namely: temperature, dust and permits that did not meet environmental quality standards. According to the Decree of the Minister of Health of the Republic of Indonesia Number 1405 / MENKES / SK / XI / 2002 concerning health requirements for office and industrial work environments. However, this condition is still feasible because it is proven that it can still support employee performance and that employees can work based on optimal parameters. Category of respondents, namely the age factor that dominates, is the age of 20-30 years which is included in the productive age in terms of work, the average education is SMK and SLTA, most of the employees are also experienced enough 3-4 years, this is very supportive of employees to be able to carry out and be responsible for each area in the factory. Employee performance appraisal at the Likert scale calculation factory is good with a value of 71% and can be seen from the production quantity of 900 tonnes / day, the quality of CPO according to standards, namely FFA 2-3 and OER 22%, timeliness of working time to produce 20 hours and experienced employees 95%. The implementation of work is sufficient in accordance with standard operating procedures (SOPs) established by management